1984
DOI: 10.1161/01.hyp.6.5.717
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of saline infusion for the diagnosis of primary aldosteronism.

Abstract: Normal subjects, normal-renin hypertensive patients, and low-renin hypertensive patients were evaluated by intravenous saline infusion and with a fludrocortisone acetate (Florinef) protocol to clarify diagnostic criteria for primary aldosteronism that are recommended for the saline infusion protocol. The patients consumed a 200 mEq sodium, 70 mEq potassium diet for 6 days, and on the last 3 days received Florinef 0.5 mg orally twice daily. On Days 3 and 6, urinary aldosterone and tetrahydroaldosterone excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(77 citation statements)
references
References 29 publications
(10 reference statements)
2
75
0
Order By: Relevance
“…Previous studies have employed mainly the saline infusion test to separate Conn's adenoma from essential hypertension (18,19,21) and were performed in hypokalaemic patients. Another study in hypokalaemic aldosteronism investigated the value of the test in differentiating both adenoma and hyperplasia from essential hypertension (34), showing a sensitivity of 96% and a specificity of 84%, which is comparable to our findings in hypokalaemic patients. In contrast, the low sensitivity of this test was recently demonstrated by Stowasser et al (3), who reported a sensitivity of 18-30% in a group of mainly normokalaemic patients with primary aldosteronism.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have employed mainly the saline infusion test to separate Conn's adenoma from essential hypertension (18,19,21) and were performed in hypokalaemic patients. Another study in hypokalaemic aldosteronism investigated the value of the test in differentiating both adenoma and hyperplasia from essential hypertension (34), showing a sensitivity of 96% and a specificity of 84%, which is comparable to our findings in hypokalaemic patients. In contrast, the low sensitivity of this test was recently demonstrated by Stowasser et al (3), who reported a sensitivity of 18-30% in a group of mainly normokalaemic patients with primary aldosteronism.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study we chose the intravenous saline loading test, which has the advantages of low cost, ease and practicability for both the patients and the clinicians, requiring only a brief outpatient visit (8,10,12). The level of normal ALD suppression by saline infusion has been commonly defined as 10 ng/ml (12,16,21), but a cut-off value of 5 ng/ ml has also been recommended (8,10,35). To minimize the possibility of misdiagnosing PA as essential hypertension, in agreement with other authors (18) we employed the cut-off value of a post-saline ALD level of 7.5 ng/dl with saline loading.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmatory test was an i.v. saline load (2 l of 0.9% NaCl infused over 4 h with the patient supine) (8,10,12). The test was considered positive if the post-test ALD levels were greater than 7.5 ng/dl (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QT intervals were corrected for the previous cardiac cycle length according to Hodges' formula: QTcH (ms)¼QT+1.75 (heart rateÀ60). 15 QTcH was considered prolonged when 4440 ms, in accordance with the criteria commonly used in the literature.…”
Section: Methodsmentioning
confidence: 99%